Grunting's competitive advantage: Considerations of force and distraction - Sinnett, Scott; Maglinti, Cj; Kingstone, Alan (PLOS ONE, 2018)
Background Grunting is pervasive in many athletic contests, and empirical evidence suggests that it may result in one exerting more physical force. It may also distract one's opponent. That grunts can distract was supported by a study showing that it led to an opponent being slower and more error prone when viewing tennis shots. An alternative explanation was that grunting masks the sound of a ball being hit. The present study provides evidence against this alternative explanation by testing the effect of grunting in a sport—mixed martial arts—where distraction, rather than masking, is the most likely mechanism. Methodology/Principal findings We first confirmed that kicking force is increased when a grunt is performed (Experiment 1), and then adapted methodology used in the tennis study to mixed martial arts (Experiment 2). Lifting the foot to kick is a silent act, and therefore there is nothing for a grunt to mask, i.e., its effect on an opponent’s response time and/or accuracy can likely be attributed to attentional distraction. Participants viewed videos of a trained mixed martial artist kicking that included, or did not include, a simulated grunt. The task was to determine as quickly as possible whether the kick was traveling upward or downward. Overall, and replicating the tennis finding, the present results indicate that a participant's response to a kick was delayed and more error prone when a simulated grunt was present. Conclusions/Significance The present findings indicate that simulated grunting may distract an opponent, leading to slower and more error prone responses. The implications for martial arts in particular, and the broader question of whether grunting should be perceived as 'cheating' in sports, are examined.